Synchronous Smooth Sliding Mode Control for Parallel Mechanism Based on Coupling Analysis. (21st March 2013) - Gao, Guoqin; Wen, Juan; Liu, Xinjun; Zhang, Zhigang
For any multi-DOF parallel mechanism, its system model is difficult to accurately establish and high-performance control is hard to achieve because of its high nonlinearity and strong coupling characteristics. In view of this, for a 6-PTRT parallel mechanism, the coupling characteristics are first analysed and then a novel smooth sliding mode control algorithm based on synchronization error is designed and the system's stability is proven - in theory - according to the Lyapunov stability theorem. By introducing the defined synchronization error into the smooth sliding mode control, the proposed method can resist the coupling effect among the branches of the parallel mechanism and realize the coordinated, synchronous and more accurate movement of each branch of the parallel mechanism with no accurate system model, whereby the tracking error of each branch may converge on zero simultaneously. The simulation results show that the synchronous smooth sliding mode control method proposed here has a shorter response time and a higher control precision when compared with the smooth sliding mode control method. By considering the errors of the adjacent branches, the synchronous coordination among the branches of the parallel mechanism with the coupling effect is effectively improved.